Local Cultures Folklore Grounded from English Textbooks for Secondary High School Indonesia - Anggraini, Ririn; Derin, Tatum; Warman, Jaka Satria; Putri, Nunung Susilo; Nursafira, Mutia Sari (Elsya : Journal of English Language Studies, 2022)
English Language Teaching (ELT) is inseparable with the teaching of the language’s culture. Indonesia has a national agenda of integrating folklore into the subject of English language in schools. Therefore, this study aims to identify the types of folklore in Indonesian EFL textbooks for secondary high school. This study collected data from 10 textbooks from Grades 7, 8, 9, 10, 11, and 12, which are published by Erlangga, Yrama Widya, Yudhistira, PT Tiga Serangkai Pustaka Mandiri, and Kemdikbud. The data analysis method was content analysis. Results showed that Indonesian EFL textbooks for secondary high school level contains 5 genres of folklore, namely fables, fairy tales, folktales, legends and myths. This study found that the most dominant type of folklore in the textbooks are legends 12 (36,3%), followed by folktales 11 (33,3%), fairy tales 5 (15,1%), fables 3 (9,3%), and lastly myths 2 (6,0%). All genres covered the cultural heritage of nearly every island and major city in Indonesia, including other countries such as Vietnam, Serbia, German and Japan. This means that Indonesia is succeeding in carrying out the national agenda of preserving students' cultural awareness and local wisdom through the teaching of folktales in ELT. The findings of this study are useful to support and enrich cultural elements integrated in English textbooks particularly the for the teaching of folklore in Indonesian EFL classrooms.